Metallic nano-structures for nano-electronic and nano-photonic applications - Hubarevich, Aliaksandr (2016)
In this thesis, thin nano-porous metallic structures are investigated in terms of the highly transparent conductive layers (TCLs) and absorbing coating in the visible wavelength range (400 to 750 nm). The finite-difference-time-domain method was used for simulation of the transmittance, reflectance and absorbance of nano-porous metallic TCLs and absorbing coatings, while percolation theory was applied for calculating of the sheet resistance of TCLs. The average transmittance of 10 to 60% in 400 to 800 nm wavelength range and the sheet resistance of 10 to 1000 Ohm/sq have been obtained for Al mesh with disordered pores arrangement. It is found that transmittance of uniformly arranged porous mesh is increased up to 80 to 90% with the conductivity range of 25 to 100 Ohm/sq. The obtained results demonstrate porous aluminum mesh as a strong candidate of low-cost transparent conductive electrode, especially for flexible electronics. The theoretical comparison of optical and electronic properties of aluminum and silver nano-porous thin layers in terms of the arrangement and size of the pores is presented. The uniform nano-porous layers exhibit a slightly higher average transmittance (up to 10%) in the wavelength range of the plasmonic response in comparison to the randomly arranged ones. Compared to uniform nano-porous layers, a much larger sheet resistance (up to 12 times) for random nano-porous layers is observed. The uniform and random Ag nano-porous layers possessing the strong plasmonic response over the whole visible range can reach an average transmittance of 90 and 80% at the sheet resistance of 10 and 20 Ohm/sq, respectively, which is comparable to widely used ITO electrodes. Influence of surface plasmons induced by localized surface plasmons (LSPs) and surface plasmon polaritons (SPPs) on the transmittance of thin uniformly arranged silver, gold and aluminum nano-porous and bulk layers are investigated. The results show that the transmittance at plasmonic wavelength is mainly affected by LSPs and SPPs at the thickness of the metal layer smaller than plasmon penetration depth. Furthermore, LSPs result in the surface plasmon waves interfering with each other in constructive or destructive ways depending on the distance between two nearest pores which leads to a change in the transmittance. Different behavior is observed when the film thickness exceeds the penetration depth: the influence of LSPs on the transmittance becomes negligible in comparison with SPPs. The given explanation grants the opportunity of novel and more detailed analyzing and construction of the nano-patterned transparent layers. An thin nano-structured plasmonic light absorber with an insulator-metal-insulator-metal (IMIM) architecture is designed and numerically studied. The IMIM structure is capable to absorb up to about 82.5% of the visible light in a broad wavelength range of 300-750 nm. The absorption by the bottom metal is only 6% of that of the top metal. The results show that the IMIM architecture has weak dependence of the angle of the incident light. By varying the top insulator material the optical absorption spectrum can be shifted more than 180 nm as compared to the conventional air-metal-insulator-metal structure. The IMIM structure can be applied for different plasmonic devices with improved performance.